The prevalence of non-GII.4 norovirus genotypes in acute gastroenteritis outbreaks in Jinan, China - Liu, Lanzheng (PLoS One, 2018)
Noroviruses (NoVs) are the leading cause of acute viral gastroenteritis outbreaks. From June 2015 to March 2017, fifteen outbreaks of acute gastroenteritis (AGE) were reported to the Jinan Center for Disease Control and Prevention in China. To identify the circulating NoV genotypes associated with outbreaks in Jinan, China, 414 specimens from the 15 outbreaks were collected and analyzed for the causative viruses, and phylogenetic analysis was performed on the NoV-positive strains. The NoV detection rate was 57.5% (238/414), and a total of 14 outbreaks were caused by NoVs (eight by infection with genogroup II (GII), five by mixed infection with GI and GII, and one by mixed infection with GII and rotavirus (RoV)-A). A total of 75 NoV sequences were obtained from 13 NoV-positive outbreaks and classified into seven genotypes (38 GII.17, 13 GII.2, 4 GII.3, 4 GII.1, 10 GI.6, 5 GI.5 and 1 GI.3), while GII.4 was not identified. The most prevalent genotype changed yearly during the 2015–2017 period. Phylogenetic analysis demonstrated that these NoV genotypes had high homology with the strains circulating worldwide, especially strains from Asian countries and cities. Our study illustrated that multiple non-GII.4 NoV genotypes were prevalent in outbreaks of AGE in Jinan, China. Year-round surveillance of multiple NoV genotypes could help health authorities reduce the impact of NoV outbreaks on public health.